2020
DOI: 10.1021/acsanm.9b02509
|View full text |Cite
|
Sign up to set email alerts
|

Magnesia and Magnesium Aluminate Catalyst Substrates for Carbon Nanotube Carpet Growth

Abstract: Carbon nanotube (CNT) carpet growth behavior is systematically investigated on a pristine and ion beam-bombarded family of basic catalyst substrates: MgAl 2 O 4 (100), MgAl 2 O 4 (110), MgAl 2 O 4 (111), and MgO (100). Interrelationships between physicochemical properties of catalyst substrates (composition, phase, basicity, and surface structure) and CNT carpet growth efficiency (catalyst lifetime and CNT growth rate) for a conventional feedstock (C 2 H 4 ) and an industrial waste (a gaseous product mixture f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Analysis of the growth profiles in Figure e provides a better understanding of the catalytic performance (activity and lifetime) at the different temperatures. The evolution of nanotube carpet height with time is generally characterized by a high growth rate at the onset that subsequently decreases gradually until complete growth termination occurs. ,, Futaba et al showed the growth profile of SWCNT carpets during “supergrowth” to be analogous to the radioactive decay process whereby catalysts lose their activity over time. Therefore, SWCNT carpet growth can be modeled by the radioactive decay model (eq ): where H is the carpet height at various times, t , while fitting parameters β and τ 0 represent the initial growth rate and characteristic catalyst lifetime, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the growth profiles in Figure e provides a better understanding of the catalytic performance (activity and lifetime) at the different temperatures. The evolution of nanotube carpet height with time is generally characterized by a high growth rate at the onset that subsequently decreases gradually until complete growth termination occurs. ,, Futaba et al showed the growth profile of SWCNT carpets during “supergrowth” to be analogous to the radioactive decay process whereby catalysts lose their activity over time. Therefore, SWCNT carpet growth can be modeled by the radioactive decay model (eq ): where H is the carpet height at various times, t , while fitting parameters β and τ 0 represent the initial growth rate and characteristic catalyst lifetime, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Maximum fitted carpet heights predicted from the product of the two fitting parameters in the model (β and τ 0 ) are 243 μm at 650 °C, 599 μm at 700 °C, 179 mm at 750 °C, and 923 μm at 800 °C. We assume that the catalyst lifetime for growth at 750 °C is longer than 90 min because growth termination during FTS-GP CVD does not appear to be instantaneous. ,, Therefore, except for growth at 750 °C, maximum fitted carpet heights are within the same range as experimental carpet heights for the growth temperatures. In other words, maximum carpet heights are most likely attained for growth at 650, 700, and 800 °C, and are significantly lower than the theoretical carpet height at 750 °C, as well as the experimental height of ∼4 mm after 90 min of growth.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Conventional carbon feedstocks (ethylene and 1% acetylene in helium) and our recently developed feedstock (FTS-GP) were used for this investigation. FTS-GP has the ability to support a high growth rate and an exceptionally long catalyst lifetime. , Over the duration of an experiment, growth rate, yield, and temperature can be monitored via in situ Raman spectroscopy using the same laser for heating. Raman spectra were acquired every 5 s and experiments were allowed to progress until SWCNT growth seemed to terminate, which was evidenced by a plateauing of the intensity of the SWCNT Raman peak (G-band).…”
Section: Methodsmentioning
confidence: 99%
“…In light of the range of parameters that affect CVD growth, rapid experimentation is a powerful tool for investigating favorable conditions that promote selective growth of small-diameter SWCNTs. Here, we utilize the Autonomous Research System (ARES)an automated, high throughput, laser-induced CVD system with in situ Raman spectral feedbackto probe the combined role of Ru as a catalyst promoter and a type of feedstock in the growth of small-diameter SWCNTs using conventional feedstocks (ethylene and acetylene) and a gaseous product mixture from Fischer-Tropsch synthesis (FTS-GP), , our new feedstock that offers potential for scale-up. We demonstrate through over 200 growth experiments that the deposition of 0.1 nm-thick Ru on a Co catalyst film (1 nm total thickness) nearly doubles the selectivity of SWCNTs with diameters below 1 nm as determined by multiexcitation Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Substrates of different nature and morphology are evidenced as suitable for the growth of VACNT due to easy-to-analyze or easy-to-industrialize properties. Various substrates have been used for the growth of VACNT, such as silicon wafers [9,24,31,34,35], quartz [36], aluminium foil [13,37,38], piezoelectric aluminium nitride film [39], stainless steel [40], titanium wire [41], magnesia and magnesium aluminate [42], as well as carbon fiber cloth [36,[43][44][45] or paper [46,47], graphite [5,48], graphene paper [49] or oxide [50], reticulated carbon foam [51], and many others [21,52]. Among all, commercial fibrous carbon 3D substrates (CF tow, cloth, felt, paper, or other woven or non-woven fabrics) are advantageous since they possess exceptionally high mechanical strength and well-defined anisotropic thermal and electrical properties [53].…”
Section: Substrates For Growth Of Vacntmentioning
confidence: 99%